PENGARUH EXPERIENTIAL MARKETING DAN BRAND TRUST TERHADAP KEPUASAN KONSUMEN DAN LOYALITAS PELANGGAN HOTEL GRAND JATRA PEKANBARU - Adithya Fajar Yufizar; Sri Restuti; Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to analyze Experiential Marketing, Brand Trust on Customer Satisfaction and Customer Loyalty, research applied on customer Grand Jatra Hotel in Pekanbaru City. The object of this research was Customer Grand Jatra Hotel in Pekanbaru City. This research consists of four variables: the dependent variable, one intervening variable and two independent variables. They are Customer Loyalty(Y2), Customer Satisfaction (Y1), Brand Trust (X2), and Experintial Marketing (X1). This research was conducted using a sample of 100 people. This research used nonprobability sampling, based on respondents who had check-in Grand Jatra Hotel over than one time. Data are taken by giving respondents structural questionaires. In terms of data analysis, this research used Path Analysis method using SPSS (Statistical Package for Social Science) version 20.Based on the hypothesis test conducted, research shows that Experiential Marketing has significant and positive effect toward Customer Satisfaction, Brand Trust has significant and positive effect toward Customer Satisfaction. Experintial Marketing has significant and positive effect toward Customer Loyalty, Brand Trust has significant and positive effect toward Customer Loyalty and Customer Satisfaction has significant and positive effect toward Customer Loyalty. Experiential Marketing and Brand Trust Influence Customer Loyaltyare moderated by Customer Satifastion.Keywords: Experiential Marketing, Brand Trust, Customer Satisfaction and Customer Loyalty.